2021
DOI: 10.1177/0956462420968994
|View full text |Cite
|
Sign up to set email alerts
|

High rates of unprotected receptive anal sex and vulnerabilities to HIV infection among Brazilian men who have sex with men

Abstract: This study aimed to evaluate unprotected receptive anal sex intercourse (URAI) rates and vulnerabilities to HIV infection among men who have sex with men (MSM) that use geosocial networking dating apps in Brazil. An online, analytical, cross-sectional study was carried out with 2,250 MSM. The analyzed variables were grouped according to domains of vulnerability and analyzed by bi and multivariate statistics to calculate the Adjusted Odds Ratios (aOR). The prevalence of self-reported HIV was 7.1%; and of URAI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…Our findings showed that at-risk sexual exposure to HIV infection was present in 30.6% of the residents in Brazil and in 24.4% of the residents in Portugal, high prevalence values when compared to studies who used similar methodology prior to the pandemic [ 28 , 30 , 31 ]. Particularly, the MSM living in Brazil presented almost twice the chances of at-risk sexual exposure to HIV infection when compared to those living in Portugal.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Our findings showed that at-risk sexual exposure to HIV infection was present in 30.6% of the residents in Brazil and in 24.4% of the residents in Portugal, high prevalence values when compared to studies who used similar methodology prior to the pandemic [ 28 , 30 , 31 ]. Particularly, the MSM living in Brazil presented almost twice the chances of at-risk sexual exposure to HIV infection when compared to those living in Portugal.…”
Section: Discussionmentioning
confidence: 50%
“…We noticed that practices classically associated with greater chances of engaging in at-risk sexual exposure to HIV infection in MSM, such as having had multiple partners [ 33 ], group sex [ 34 ], not knowing the partner’s serological status [ 28 ] and practicing chemsex [ 35 ] were also determining factors when we consider the COVID-19 pandemic scenario, although a reduction in part of these behaviors could be expected following the promotion of social distancing and isolation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The form was content validated ( 25 ) by three expert/specialist in the topic and was divided into four sections with 46 questions, most were multiple-choice questions, and some were mandatory; without answering those questions, the participant could not proceed with the questionnaire. The questions addressed social and demographic information (age, education, gender identity, housing and type of relationships, according to prior studies) ( 10 - 11 , 26 - 27 ) , mental health (self-perception of stress and strategies to cope with the pandemic), behaviors adopted to protect against the pandemic (social distancing, protective measures against the COVID-19 and level of adherence) and sexual behavior during the social distancing, isolation or quarantine (casual sex, adoption of protective measures against the COVID-19 and sexually transmissible infections [STIs], and type and number of sexual partners) and in the period immediately before the emergence of the pandemic (strategies to find partners, type and number of partners and preventive measures against STIs).…”
Section: Methodsmentioning
confidence: 99%